Financial bookkeeping training for MSMEs in South Cipinang Besar Flats, East Jakarta - Marini Anggie Putri Siregar; Amrizal Sutan Kayo; Dini Amalia; Gusmiarni Gusmiarni; Ida M Ibrahim; Monika Budiman; Yohn Piter Barus; Pandu Haryanto; Nur Rahmah Wati; Dhefitriana Azzahra Kartika (Journal of Community Service and Empowerment, 2025)
Many Micro, Small, and Medium Enterprises (MSMEs) in the South Cipinang Besar Flats, East Jakarta, face challenges in managing bookkeeping due to limited knowledge and lack of access to adequate recording tools. As a result, they often struggle with financial bookkeeping, business planning, and applying for financial assistance or loans. This community service activity aimed to provide training on basic bookkeeping for MSMEs to help them understand how to record transactions and gain broader insights into financial management. The training was conducted in one day and received a positive response and high enthusiasm from participants. The results showed an improvement in basic accounting knowledge, increased motivation to record purchase and sales transactions, the ability to calculate the cost of goods sold, and a better understanding of bookkeeping relevant to their business needs. Participants felt supported by the training, which helped them manage their finances more effectively. The ability to maintain proper bookkeeping is also expected to support MSMEs in preparing documents for loan applications and accessing funding opportunities in the future. For sustainability, further mentoring is needed to help MSME actors continue developing their skills, knowledge, and creativity in managing business finances.